The Relationship Between Social Support with Psychological Well-Being in Tamping Class IIA Correctional Institutions Padang - Monica Apriyuni; Anindra Guspa; Apriyuni, Monica (Causalita, 2024)
The aim of this research is to determine the relationship between social support and psychological well-being in Tamping (Accompanying Prisoners). This research design uses quantitative correlational research with the population in this study being all Tamping (Accompanying Prisoners) at the Class IIA Padang Correctional Institution. The sampling technique used was total sampling where the entire population was sampled with a total of 39 Tamping (Accompanying Prisoners). This research uses a scale measuring tool for social support and psychological well-being with variable reliability values ​​of 0,822 and 0,840. The data analysis technique uses Product Moment Correlation, the results of which show that there is a positive relationship between social support and psychological well-being in Tamping (Accompanying Prisoners) at the Class IIA Padang Correctional Institution with a correlation value (r) of 0,775 and a significance value (p) of 0,000.